Ex vivo manipulation of bone marrow cells to rescue uremia-induced dysfunction for autologous therapy - Grange, Cristina (Stem Cell Res Ther, 2015)
Uremic toxins are known to affect the regenerative properties of tissue-resident and circulating stem cells and thus appear to be a limiting factor for autologous stem cell-based approaches for treating chronic kidney disease. The recent article by van Koppen and colleagues in Stem Cell Research & Therapy provides evidence that an ex vivo short-term pre-treatment with statins reverts the dysfunction of bone marrow stem cells isolated from rats with renal impairment. Indeed, statin pre-treated cells improved renal function in a model of established chronic kidney disease. Our commentary discusses the potential of this approach in the context of autologous cell therapy and the available knowledge on the mechanisms involved in uremia-induced stem cell dysfunction.